Legal frameworks in the built environment - Badman, Jean; Grimmett, Laurie (Built environment series of textbooks, 1996)
Law is a complex subject and has major impacts on the built environment and all those working in it. Law is seen as one of the strongest interdisciplinary links between the various professions; it is essential to have a clear understanding of how both statute and common law, as well as the legislative frameworks (statutory controls/policy and procedures), affect all the roles/areas throughout the built environment. This book will provide students with a broad understanding of the law and its applications, from disputes to land use.